MINAT KARIER ANAK MELALUI ART THERAPY: STUDI KASUS DALAM PERSPEKTIF BIMBINGAN DAN KONSELING - Rahmawati; Muchammad Achsanul Hakim; Tri Prasetiyowati; Putri Inayah; Najlatun Naqiyah; Denok Setiawati (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study explores the role of Art therapy in expressing career interests among marginalized children aged 7–12 years within the context of group counseling services. Using a qualitative intrinsic case study approach, the research focuses on understanding the subjective experiences of children from underprivileged backgrounds in Surabaya, Indonesia. Data collection involved participatory observation, documentation of children’s drawings, and spontaneous verbal expressions during art activities. The findings reveal that through art therapy, children were able to symbolize their future aspirations, such as becoming doctors, soldiers, soccer players, singers, and entrepreneurs, despite facing socioeconomic challenges. Art therapy not only facilitated the expression of career dreams but also enhanced self-concept, motivation, and self-confidence. The study highlights the effectiveness of group Art therapy as a psycho-pedagogical intervention in non-formal education, providing marginalized children with a safe and empowering medium for self-exploration and future orientation. Consequently, Art therapy is recommended as an inclusive, accessible strategy for fostering the personal and educational development of vulnerable youth.